Evaluation of intellectual disabilities - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Individuals who have limited communication skills, poor memory, and decreased social reasoning skills are those who have intellectual disability (ID) and have special needs in the criminal justice system as well as in many aspects of their lives. The disability in intellectual skills includes a wide range in the developmental spectrum from mild to severe and requires comprehensive evaluations for each category. Individuals with ID are more often victims of crime compared to individuals without ID. However, they also have increased vulnerability in committing crimes. In terms of social rights, many countries have treatment services and legal regulations for individuals with ID. Although the legal regulations for ID individuals are quite old historically, there continues to be difficulties in identifying individuals with ID and the need to improve the understanding of their needs in different stages of the justice system. This chapter contains information about the definition of ID, its scope, the diagnostic process, how individuals with ID are involved in criminal justice, and recommendations on how to conduct a forensic interview that addresses the developmental, social, and emotional needs of individuals with ID. It also focuses on the differential diagnosis of malingering and ID with the use of clinical evaluations and test batteries. © 2021 Nova Science Publishers, Inc.